Intercultural Interpretation: The Study of the Qur'an in Translation of the Islamic University of Indonesia 2020 Edition - Imam Nawawi (AQWAL Journal of Qur'an and Hadis Studies, 2021)
This study examines the translation of the Quran by H. Zaini Dahlan edited by KH.Ahmad Bahauddin Noersalim, published by UII Press Yogyakarta 2020. Thisqualitative type of research uses a literature research design with a multidisciplinaryapproach; translation theory, language logic, language structure, and socio-linguisticspace. This study found six (6) main points: first, the problematic problem oftranslating the UII version of the Quran, second, meaningful translation, third, the useof language logic, fourth, the influence of Arabic syntax, fifth, the creation of space,character and reader hierarchy, and sixth, originality and local cultural wisdom.